2017
DOI: 10.1111/jsr.12605
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic basal forebrain structures are not essential for mediation of the arousing action of glutamate

Abstract: The cholinergic basal forebrain contributes to cortical activation and receives rich innervations from the ascending activating system. It is involved in the mediation of the arousing actions of noradrenaline and histamine. Glutamatergic stimulation in the basal forebrain results in cortical acetylcholine release and suppression of sleep. However, it is not known to what extent the cholinergic versus non-cholinergic basal forebrain projection neurones contribute to the arousing action of glutamate. To clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The basal forebrain, a region wherein KYNA was both elevated with kynurenine challenge and reduced with PF-04859989 pre-treatment, is richly implicated in modulation of sleep and arousal behavior. 5052 A large amount of acetylcholine is released from the basal forebrain during REM sleep, 5355 and we postulate that KYNA-mediated modulation of cholinergic neurotransmission may impede these dynamics. 56 Within the extracellular milieu, KYNA is present within low micromolar concentrations and optimally positioned to inhibit receptor targets including α7nACh receptors and NMDA receptors.…”
Section: Discussionmentioning
confidence: 90%
“…The basal forebrain, a region wherein KYNA was both elevated with kynurenine challenge and reduced with PF-04859989 pre-treatment, is richly implicated in modulation of sleep and arousal behavior. 5052 A large amount of acetylcholine is released from the basal forebrain during REM sleep, 5355 and we postulate that KYNA-mediated modulation of cholinergic neurotransmission may impede these dynamics. 56 Within the extracellular milieu, KYNA is present within low micromolar concentrations and optimally positioned to inhibit receptor targets including α7nACh receptors and NMDA receptors.…”
Section: Discussionmentioning
confidence: 90%
“…Incorporating multiple probes, especially commercially purchased probes, can expedite experimental progress at the expense of collecting data that overlooks localized neurochemical fluctuations. Most of these published experiments have been conducted in rodents while utilizing commercially-available microdialysis probes in separate locations from the brain-penetrating electrodes [96,102,104,[106][107][108][109][110][111][112][113][114] despite evidence that extracellular biomarker diffusion is severely limited by tissue resistance [51,110]. Therefore, it is crucial that the neurochemical sampling probe is spatially coincident with the target neurons to properly correlate fluctuations in analytes with electrophysiology data.…”
Section: Discussion and Open Challengesmentioning
confidence: 99%
“…Several microdialysis and microperfusion electrodes have been designed and tested to tackle the in vivo sensing challenge of simultaneously measuring changes in biomarkers during passive electrophysiological recording or active electrical stimulation of brain tissue [16,[95][96][97][98][99][100][101][102][103][104][105]. Some of the more elementary designs involve two separate probes for neurochemical sampling and EEG recording [95,96,102,104,[106][107][108][109][110][111][112][113][114]. Other designs successfully incorporate both technologies into a single probe [98][99][100][101]103] or even fix separate probes together through various means [115][116][117][118][119][120][121].…”
Section: Previously Fabricated Microdialysis and Microperfusion Electrode Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological studies have suggested that BF glutamatergic neurons excite local cholinergic and PV-expressing GABAergic neurons and that cholinergic neurons also excite nearby PV-expressing GABAergic neurons, thus forming a hierarchical excitatory microcircuit; this may partially mediate the strong wake-promoting effect of glutamatergic neurons [ 21 ]. Lesions within local BF cholinergic neurons barely impede glutamatergic neurons from robustly promoting wakefulness, indicating the involvement of long-range projections [ 31 ]. In addition, an opto-dialysis study showed that infusion of cholinergic antagonists within the BF could prevent the wake-promoting effect of activation of BF cholinergic neurons [ 32 ], indicating the involvement of local non-cholinergic neurons in the cholinergic regulation of sleep and wakefulness.…”
Section: Basal Forebrainmentioning
confidence: 99%